Term live secondary abdominal pregnancy: a case report - Swain, Sujata; Behuria, Sasmita; Satpathy, Rabi Narayan; Venkatachalapathy, Abarajda; Mahapatra, Purna Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
An abdominal pregnancy is defined as an ectopic pregnancy that implants in the peritoneal cavity. Abdominal pregnancy is a rare form of ectopic pregnancy and is frequently misdiagnosed. Advanced abdominal pregnancy is a rare event, with high fetal and maternal morbidity and mortality. We report a case of abdominal pregnancy leading to a delivery of a healthy baby girl weighing 1.75 kg. A 35 year old woman, gravida 2 para 1 was referred from a private hospital as a case of term pregnancy with transverse lie, placenta praevia and severe oligohydraminos (AFI-3) with complaints of severe abdominal pain for one day. The patient suffered from recurrent abdominal pain with painful fetal movements throughout her pregnancy. Diagnosis was missed inspite of ultrasound examination. Intraoperatively it was diagnosed to be a case of abdominal pregnancy, where we delivered a healthy baby without any difficulty. Deattached placenta was removed in piecemeal. There occurred severe torrential bleeding was managed by peritoneal packing. Both mother & foetus survived due to timely management & quick surgical decision. Patient was followed regularly with serum β HCG level.